Same Target from Different Angles? Anti-discrimination, Protection of Minorities and the Rights of Indigenous Peoples in the UN - Szalai, Anikó (Pécs journal of international and European law, 2014)
In the past decades the United Nations (UN) elaborately dealt with the issues of discrimination, besides adopting many resolutions, three major documents came to life: the 1965 International Convention on the Elimination of All Forms of Racial Discrimination, the 1992 Declaration on the Rights of Persons Belonging to National or Ethnic, Religious and Linguistic Minorities and the 2007 Declaration on Indigenous Peoples. This paper shows the evolution of the three different angles of protection, compares the documents, analyses the differences and discusses whether the included rights could be integrated into one regime of protection.